2000
DOI: 10.1258/0956462001915002
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cytology screening for sexually-active teenagers

Abstract: Our aim was to determine the value of cervical cytology for sexually-active teenagers attending genitourinary medicine (GUM) clinics. This is a retrospective review of 57,093 women who had cervical cytology reported at the Royal Bolton Hospital (RBH) during the period 1 April 1994 to 31 March 1996. The results were subdivided into 2 age groups; < or = 19 years and > or = 20 years. Cervical cytology abnormalities within each age group were analysed and compared with the national figures for cervical cytology sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The authors reported higher 'major abnormalities' of smears performed at Bolton GU medicine clinics than the national average (37/1000 compared with 12/1000 young women at the age of 20 and above). 9 The risk of cervical smear abnormalities was reported to be higher in women with concomitant genital infections, 10 which is supported by other research on risk factors. 3 The British Co-operative Clinical Group for Genitourinary Medicine explored routine and opportunistic cervical cytology, undertaken within GU medicine clinics.…”
Section: Clinical Basis Of Providing Cervical Cytology In Gu Medicinementioning
confidence: 63%
“…The authors reported higher 'major abnormalities' of smears performed at Bolton GU medicine clinics than the national average (37/1000 compared with 12/1000 young women at the age of 20 and above). 9 The risk of cervical smear abnormalities was reported to be higher in women with concomitant genital infections, 10 which is supported by other research on risk factors. 3 The British Co-operative Clinical Group for Genitourinary Medicine explored routine and opportunistic cervical cytology, undertaken within GU medicine clinics.…”
Section: Clinical Basis Of Providing Cervical Cytology In Gu Medicinementioning
confidence: 63%